Increased Mortality Rate in Patient with Frothy Sputum After Tof Total Correction Surgery - Suprayitno Wardoyo; Dhama Shinta Susanti; Aflah Dhea Bariz Yasta; Rendy Agustian; Laksana Paduan Wilangsoka (Journal Research of Social Science, Economics, and Management, 2022)
Tetralogy of Fallot (TOF) is the most common congenital heart disease. The most common risk factor for TOF is Down syndrome(DS). There are two management approaches for TOF: medication and operation. Operation/surgical treatment is consisted of palliative shunt and definitive repair. In several case patients with TOF develop collaterals or major aortopulmonary collateral arteries (MAPCAs), which can lung overflow can be initiated after surgery procedure was completed. This causes the CPB time in the repair operation to be long so that the risk of RV/LV dysfunction due to ischemic use of the CPB machine is very high. Frothy sputum is the one of signs of lung injury that related to left and/or right ventricular dysfunction, it may increased mortality in patients TOF repaired. The aim of this study was to identify frothy sputum associated with mortality in patient repaired of TOF. This study is cross-sectional study. We collect data retrospectively through medical record list from 2019 to 2020.  In our study, there were 32 patients data included, consisted with more dominant male (n = 22) compare to female (n = 10). It was found that 7 female patients and 9 male patients experienced frothy sputum after TOF repair surgery. There are association not only mortality (p-value 0.033) but also frothy sputum with pulmonary regurgitation (p-value 0.049). Although any result of the study and weakness described previously, the study can be as basis for futher research so that an appropiate guideline can be established to deal frothy sputum in patients TOF repaired.